Power decoupling control for capacitance reduction in cascaded-H-bridge-converter-based regenerative motor drive systems - Yang, Zezhou (2021)
A cascaded H-bridge (CHB) converter-based medium or high-voltage motor drive system, that consists of three single-phase CHB chains, may suffer a severe second-harmonic ripple power issue. Oversizing dc capacitors and using active power decoupling control with additional active or passive components are the two possible ways to address this issue, but this is achieved at the expense of increased system cost and complexity. This paper proposes a power decoupling control to tackle this issue without using any extra components for regenerative CHB-based converters. By introducing a set of negative-sequence decoupling currents to the front-end pulsewidth-modulated rectifier of each submodule, the second-harmonic ripple power can be removed from the submodule dc capacitors, and all the ripple power in the transformer core legs can be counteracted without affecting the magnetic flux and the grid current. The decoupling current is derived from the input and output measurements of the CHB converter. It gives the minimal increase of the modulation index and has no impacts on the input and output power quality. The effectiveness of the proposed control is verified in simulations and a 72-kW experimental prototype.